# Please Explain and Solve how to do these questions in this picture

1
by Ugoel911
from which book id you ask/
it is my Holiday Homework

2015-05-30T21:31:54+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Factor theorem says that  if  x - a is a factor of   f(x)  if and only if  f(a) = 0...

F(x) = x^n  + a^n
F(-a) = -(1)^n a^n + a^n   =   0   for   odd   n...  as  -1)^n  = -1..
hence  x + a is a factor of  F(x)

===================
F(x) =  x⁴  - 4 / x⁴  =  (x⁸ - 4) / x⁴
Let    a = √√2  = (2)¹/⁴
then  a² = √2  and  a⁴ = 2      then  a⁸ = 4

F(a) =  (a⁸ - 4) / a⁴  = 0          =>  x - a  is a factor of  F(x)
F(x)  =  (x - a) (x⁷ + b x⁶ + c x⁵ + d x⁴ + e x³ + f x² + g x + 4/a) / x⁴
=  [x⁸ + (b-a) x⁷ + (c-ab) x⁶ + (d-ac) x⁵ + (e-ad) x⁴ + (f - ae) x³
+ (g - af) x² + (4/a - ag) x - 4 ] / x⁴
= (x⁸ - 4) / x⁴

=> b = a
c = ab = a² = √2
d = ac = a³ = 2³/⁴
e = ad =a⁴ = 2
f = ae =  a⁵ = 2⁵/⁴
g =   a⁶ = 2³/²

4/a = ag = a⁷      =>  a⁸ = 4.. which i s  true,,

F(x) =  (x - a) (x⁷ + a x⁶ + √2 x⁵ + a³ x⁴ + 2 x³ + 2⁵/⁴ x² + 2³/² x + 4/a) / x⁴
=  (x - a) (x³ + a x² + √2 x + 2³/⁴ + 2 x⁻¹ + 2⁵/⁴ /x⁻² + 2√2 x⁻³ + 4/a x⁻⁴)

Factorizing :
F(x) = (x⁸ - 4) / x⁴  = (x⁴ - 2) (1 + 2 x⁻⁴)
= (x² - √2) (x²  + √2) (1 + 2 x⁻⁴)
=  (x - a) (x + a) (x² + √2) (a + 2 x⁻⁴)

where a² = √2
=================================

x+2  is a factor of   F(x) = (x + 1)⁷ + (2x + k)³
=>  F(-2) = 0
=>  -1⁷ + (k-4)³  = 0
=>  k-4 = 1
=>  k = 5

===================

divisor    x^2 + x - 12 = (x + 4) (x - 3)
Let    x^3 - 6 x^2 - 15 x + 80
= (x + 4) (x - 3) *  (x + a)    +    [  b (x + 4)  +  c (x - 3) ]
Thus the remainder after division by divisor is  (b + c) x + 4 b - 3 c

Let F(x) =  x^3 - 6 x^2 - 15 x + 80 - (b + c) x - 4 b +  3 c
F(-4) = 0  as it should be divisible by x + 4
=>  -64 - 96 + 60 +  4 (b+c) - 4 b + 3c = 0
=>    c =  100/7

F(3) = 0    as F(x) is divisible by  x - 3
=>  27 - 54 - 45 + 80 - 3(b+c) - 4 b + 3 c  =  0
=>   b =  8/7

So   4 * [ 27 x - 67] /7    must be subtracted from the iven polynomial for the divisor to exatly divide it....

click on thanks button above please